Attraktive E-Learning-Angebote schnell und kostenfrei entwickeln? Kein Problem! Beispiele aus den bibliothekswissenschaftlichen Studiengängen der TH Köln - Tappenbeck, Inka; Sahler, Laura; Wüst, Janina; Mühling, Annika; Piontkowitz, Pia; Rothe, Verena; Roth, Dominique; Faust, Luisa; Schüßler, Pia; Schubert, Peter (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2019)
Using practical project work of library science students at the TH Köln as examples, this article presents possibilities of creating e-learning projects that can be realized in a short time and without a financial budget. The focus is on unconventional forms of presentation such as comic-like animated films or the presentation of library content according to the concept of “Sommer’s World Literature”. The contribution aims at encouraging libraries to experiment with new formats in the context of e-learning, which can contribute to increasing the attractiveness of library services and which can beimplemented with little time and money.